2013
DOI: 10.16910/jemr.6.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Is poor coordination of saccades in dyslexics a consequence of reading difficulties? A study case

Abstract: We hypothesize that the high quality of binocular coordination of saccades in reading is progressively learned during childhood, and this oculomotor learning is based on a synergy between saccades and vergence. In present work deficits in the binocular control of saccades in six dyslexic children (mean age was 11±2.48 years) are studied for two tasks (text reading and Xs-C scanning), and at two viewing distances (40 cm and 100 cm). Fixation durations resulting are longer in Xs-C scanning task than in text read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Anomalous eye movements have been discussed for some time now, in particular for children and adults with dyslexia [2,5] who lag behind normal readers on embedded letters and on words [6]. Binocular coordination of saccades [2,7] and vergence anomaly [8] have also been observed. Moreover, many studies have found that an excessive number of overly long fixations generally perturb dyslexics in reading but not in visual tasks [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Anomalous eye movements have been discussed for some time now, in particular for children and adults with dyslexia [2,5] who lag behind normal readers on embedded letters and on words [6]. Binocular coordination of saccades [2,7] and vergence anomaly [8] have also been observed. Moreover, many studies have found that an excessive number of overly long fixations generally perturb dyslexics in reading but not in visual tasks [9][10][11].…”
Section: Introductionmentioning
confidence: 99%